Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Land‐Use Effects on Surface Water Quality in Temperate Lowland Peatlands - Teresa Silverthorn; Dan Aberg; Francesca Baker; Chris Bell; Chris D. Evans; Caroline Gurd; Ian Holman; Graham Howell; Angus McEwen; Ross Morrison; Josh Oakley; Francesca Southon; et al. (Global Change Biology, 2026)
Peatlands are important ecosystems for carbon storage, water regulation, water quality and other valuable ecosystem services that have been heavily impacted by drainage and conversion to grassland and cropland. Rewetting, or raising of the water table closer to the ground surface, is proposed as a solution to reduce peatland subsidence and carbon losses. Both peatland drainage and peatland rewetting may have unintended impacts on water quality, either by introducing solutes from the water used for rewetting, or by leaching of substances accumulated in peat. Here, we examined the effects of land use on UK lowland peat surface water chemistry by collecting a total of 350 surface water samples from 77 individual water bodies (ditches, streams, ponds) in 2024, across 33 sites representing the range of temperate lowland peatland types. Samples were measured for a wide array of chemical determinands including: carbon (C), nitrogen (N) and phosphorus (P), heavy metals, other anions and cations, and dissolved greenhouse gas concentrations. We found some clear patterns related to land use, notably high nitrate concentrations in surface waters draining croplands. Macronutrient stoichiometry revealed similar patterns at grassland, conservation‐managed and rewetted sites indicative of N and P co‐limitation, suggesting that rewetting leads to a nutrient balance comparable to natural conditions. Peatland type (bog vs. fen) was more important than land use in explaining patterns in most ion concentrations. Site and regional histories were more important than land use for patterns of heavy metal concentrations, indicating the importance of considering regional historical industrial activity. Overall, peatland land use can be an important driver of key nutrients and their stoichiometry, with no consistent negative impacts of peatland rewetting on water quality nor greenhouse gases.

High thermotolerance to extreme marine heatwaves for four New Caledonian sponges - Barbara J. Graham; Simon K. Davy; Lisa Woods; Torsten Thomas; Riccardo Rodolfo-Metalpa; James J. Bell (Marine Pollution Bulletin, 2026)

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Harmonisation of read-across methodology for drug substance extractables and leachables (E&Ls) - Melisa Masuda-Herrera; Hannah T. Rosen; Anders Burild; Thomas Broschard; Tyler Bell; Jessica Graham; Troy Griffin; Jedd Hillegass; Penny Leavitt; Brian Huta; Patricia Parris; Uma Bruen; et al. (Regulatory Toxicology and Pharmacology, 2023)

Environmental and genetic variation in an asexual plant - Mark Davidson Jewell; Graham Bell (Aquatic Botany, 2023)

Estimating trends and magnitudes of bycatch in the tuna fisheries of the Western and Central Pacific Ocean - Tom Peatman; Valerie Allain; Lui Bell; Berry Muller; Aurélien Panizza; Naiten B. Phillip; Graham Pilling; Simon Nicol (Fish and Fisheries, 2023)
Minimising the unintended capture of fish, marine mammals, reptiles, seabirds and other marine organisms is an important component of responsible fisheries management and for stabilising declines and rebuilding populations of threatened species. The analyses presented were designed to establish the first quantitative baseline of historical catches, catch rates and species composition for the dominant tuna fisheries operating in the western and central Pacific, the world's largest in terms of tuna catch. Using records from 612,148 fishing events collected by independent ‘at sea’ observers, estimates for finfish, billfish, elasmobranchs, marine mammals and sea turtles show that the composition and magnitude of catches varied considerably by fishery type and practice for the period 2003–2019. Simulations indicated that precision in longline estimates would be improved by monitoring a proportion of fishing sets from all fishing trips rather than full coverage from a proportion of all fishing trips. While attributing reasons for temporal trends in estimated bycatch was difficult due to the confounding impacts of changing abundances and fishing practices, the trends identified the nature of potential relationships for species that are not accurately quantified, or not covered, by fishing vessel logbooks. The trends in catch estimates, and the catch rate models, have utility in identifying species which may require targeted additional analyses and management interventions, including species of conservation interest (either due to their threatened status or vulnerability to fishing) such as elasmobranchs and sea turtles. Moreover, the estimates should support future evaluations of the impact of these industrial‐scale fisheries on bycatch species.

Eco‐evolutionary contributions to community trait change in floating aquatic plants - Mark Davidson Jewell; Graham Bell (Ecology, 2023)
An entire community of organisms may become modified when its environment changes. These modifications can happen through physiological processes (plasticity), evolutionary processes (adaptation) or shifts in species composition (sorting). The outcome of these three sources of change constitutes the community's phenotypic response, but how they combine to drive community trait dynamics is not currently well understood. We have conducted a community selection experiment in which communities of short‐lived floating aquatic plants were grown in a range of stressful conditions, and measured changes in their body size. Determinants of phenotypic change were assessed with a full community reciprocal transplant which led to estimates of the contributions of plasticity, adaptation, and sorting. Species were modified during the experiment by both plasticity and adaptation, but in either case the magnitude and direction of change differed among species. Sorting and adaptation were of equal magnitude but tended to act in opposite directions: in conditions where species with large fronds prevailed, each species evolved smaller fronds, and vice versa. We conclude that community trait dynamics cannot be understood simply by extrapolating the adaptive response of any single species to the whole community.

Geographical distribution of floating aquatic plants in relation to environmental conditions in southern Quebec, Canada - Mark Davidson Jewell; Sofia J. van Moorsel; Graham Bell (Aquatic Botany, 2023)

Overwintering and re-emergence in Lemna minor - Mark Davidson Jewell; Graham Bell (Aquatic Botany, 2023)

Enhancing cooperative responses by regional fisheries management organisations to climate-driven redistribution of tropical Pacific tuna stocks - Camille Goodman; Ruth Davis; Kamal Azmi; Johann Bell; Grantly R. Galland; Eric Gilman; Bianca Haas; Quentin Hanich; Patrick Lehodey; Lara Manarangi-Trott; Simon Nicol; Pablo Obregon; et al. (Frontiers in Marine Science, 2022)
Climate change is predicted to alter the distributions of tropical tuna stocks in the Pacific Ocean. Recent modelling projects significant future shifts in tuna biomass from west to east, and from national jurisdictions to high seas areas. As the distributions of these stocks change, the relevant regional fisheries management organisations (RFMOs)—the Western and Central Pacific Fisheries Commission (WCPFC) and the Inter-American Tropical Tuna Commission (IATTC)—will need to develop an expanded framework for cooperation and collaboration to fulfil their conservation and management responsibilities under international law. The key elements of a possible expanded framework for cooperation can be developed, and fundamental areas for collaboration identified, by applying and adapting principles established in the United Nations Convention on the Law of the Sea, the United Nations Fish Stocks Agreement, and the constituent instruments of the RFMOs themselves. Our analysis reveals a wide range of important issues requiring cooperation, and three clear priorities. First, a formal mechanism for cooperation is needed to enable effective and efficient decision-making and action by the two RFMOs on key issues. Second, further cooperation is required in scientific research and modelling to better understand the biology and distributions of Pacific tuna stocks and how they will respond to climate change, and to inform stock assessments and harvest strategies. Third, the RFMOs must cooperate to define appropriate limits on fishing for each stock in a way that ensures they are compatible across the two organisations, taking into account their different members and management regimes.

Resistance, resilience, and functional redundancy of freshwater bacterioplankton communities facing a gradient of agricultural stressors in a mesocosm experiment - Naíla Barbosa da Costa; Vincent Fugère; Marie‐Pier Hébert; Charles C.Y. Xu; Rowan D.H. Barrett; Beatrix E. Beisner; Graham Bell; Viviane Yargeau; Gregor F. Fussmann; Andrew Gonzalez; B. Jesse Shapiro (Molecular Ecology, 2021)
Agricultural pollution with fertilizers and pesticides is a common disturbance to freshwater biodiversity. Bacterioplankton communities are at the base of aquatic food webs, but their responses to these potentially interacting stressors are rarely explored. To test the extent of resistance and resilience in bacterioplankton communities faced with agricultural stressors, we exposed freshwater mesocosms to single and combined gradients of two commonly used pesticides: the herbicide glyphosate (0–15 mg/L) and the neonicotinoid insecticide imidacloprid (0–60 μg/L), in high or low nutrient backgrounds. Over the 43‐day experiment, we tracked variation in bacterial density with flow cytometry, carbon substrate use with Biolog EcoPlates, and taxonomic diversity and composition with environmental 16S rRNA gene amplicon sequencing. We show that only glyphosate (at the highest dose, 15 mg/L), but not imidacloprid, nutrients, or their interactions measurably changed community structure, favouring members of the Proteobacteria including the genus Agrobacterium . However, no change in carbon substrate use was detected throughout, suggesting functional redundancy despite taxonomic changes. We further show that communities are resilient at broad, but not fine taxonomic levels: 24 days after glyphosate application the precise amplicon sequence variants do not return, and tend to be replaced by phylogenetically close taxa. We conclude that high doses of glyphosate – but still within commonly acceptable regulatory guidelines – alter freshwater bacterioplankton by favouring a subset of higher taxonomic units (i.e., genus to phylum) that transiently thrive in the presence of glyphosate. Longer‐term impacts of glyphosate at finer taxonomic resolution merit further investigation.

Embedding biodiversity research into climate adaptation policy and practice - Victoria Graham; Tony Auld; Linda Beaumont; Linda Bell; Suzanne Dunford; Rachael Gallagher; Nola Hancock; Michelle R. Leishman; Polly Mitchell; Leigh Staas; Lesley Hughes (Global Change Biology, 2021)
Addressing climate change risks requires collaboration and engagement across all sectors of society. In particular, effective partnerships are needed between research scientists producing new knowledge, policy‐makers and practitioners who apply conservation actions on the ground. We describe the implementation of a model for increasing the application and useability of biodiversity research in climate adaptation policy and practice. The focus of the program was to increase the ability of a state government agency and natural resource practitioners in Australia to manage and protect biodiversity in a changing climate. The model comprised a five‐stage process for enhancing impact (i) initiation of research projects that addressed priority conservation policy and management issues; (ii) co‐design of the research using a collaborative approach involving multiple stakeholders; (iii) implementation of the research and design of decision tools and web‐based resources; (iv) collaborative dissemination of the tools and resources via government and community working groups; and (v) evaluation of research impact. We report on the model development and implementation, and critically reflect on the model's impact. We share the lessons learnt from the challenges of operating within a stakeholder group with diverse objectives and criteria for success, and provide a template for creating an environmental research program with real world impact.

Correction to: Rethinking soil water repellency and its management - Katinka X. Ruthrof; Anna J. M. Hopkins; Melissa Danks; Graham O’Hara; Richard Bell; David Henry; Rachel Standish; Mark Tibbett; John Howieson; Treena Burgess; Richard Harper (Plant Ecology, 2020)

Rethinking soil water repellency and its management - Katinka X. Ruthrof; Anna J. M. Hopkins; Melissa Danks; Graham O’Hara; Richard Bell; David Henry; Rachel Standish; Mark Tibbett; John Howieson; Treena Burgess; Richard Harper (Plant Ecology, 2019)

Patterns of population structure and complex haplotype sharing among field isolates of the green alga Chlamydomonas reinhardtii - Rory J. Craig; Katharina B. Böndel; Kazuharu Arakawa; Takashi Nakada; Takuro Ito; Graham Bell; Nick Colegrave; Peter D. Keightley; Rob W. Ness (Molecular Ecology, 2019)
The nature of population structure in microbial eukaryotes has long been debated. Competing models have argued that microbial species are either ubiquitous, with high dispersal and low rates of speciation, or that for many species gene flow between populations is limited, resulting in evolutionary histories similar to those of macroorganisms. However, population genomic approaches have seldom been applied to this question. Here, we analyse whole‐genome resequencing data for all 36 confirmed field isolates of the green alga Chlamydomonas reinhardtii . At a continental scale, we report evidence for putative allopatric divergence, between both North American and Japanese isolates, and two highly differentiated lineages within N. America. Conversely, at a local scale within the most densely sampled lineage, we find little evidence for either spatial or temporal structure. Taken together with evidence for ongoing admixture between the two N. American lineages, this lack of structure supports a role for substantial dispersal in C. reinhardtii and implies that between‐lineage differentiation may be maintained by reproductive isolation and/or local adaptation. Our results therefore support a role for allopatric divergence in microbial eukaryotes, while also indicating that species may be ubiquitous at local scales. Despite the high genetic diversity observed within the most well‐sampled lineage, we find that pairs of isolates share on average ~9% of their genomes in long haplotypes, even when isolates were sampled decades apart and from different locations. This proportion is several orders of magnitude higher than the Wright–Fisher expectation, raising many further questions concerning the evolutionary genetics of C. reinhardtii and microbial eukaryotes generally.

The role of managed natural spaces in connecting people with urban nature: a comparison of local user, researcher, and provider views - Siân de Bell; Hilary Graham; Piran C. L. White (Urban Ecosystems, 2018)

The ghosts of selection past reduces the probability of plastic rescue but increases the likelihood of evolutionary rescue to novel stressors in experimental populations of wild yeast - Pedram Samani; Graham Bell (Ecology Letters, 2016)
Persistence by adaptation is called evolutionary rescue. Evolutionary rescue is more likely in populations that have been previously exposed to lower doses of the same stressor. Environmental fluctuations might also reduce the possibility of rescue, but little is known about the effect of evolutionary history on the likelihood of rescue. In this study, we hypothesised that the ubiquitous operation of generalised stress responses in many organisms increases the likelihood of rescue after exposure to other stressors. We tested this hypothesis with experimental populations that had been exposed to long‐term starvation and were then selected on different, unrelated stressors. We found that prior adaptation to starvation imposes contrary effects on the plastic and evolutionary responses of populations to subsequent stressors. When first exposed to new stressors, such populations become extinct more often. If they survive the initial exposure to the new stressors, however, they are more likely to undergo evolutionary rescue.

CO2 alters community composition and response to nutrient enrichment of freshwater phytoplankton - Etienne Low-Décarie; Graham Bell; Gregor F. Fussmann (Oecologia, 2015)

An ocean observation system for monitoring the affects of climate change on the ecology and sustainability of pelagic fisheries in the Pacific Ocean - Simon J. Nicol; Valerie Allain; Graham M. Pilling; Jeff Polovina; Marta Coll; Johann Bell; Paul Dalzell; Peter Sharples; Robert Olson; Shane Griffiths; Jeffrey M. Dambacher; Jock Young; et al. (Climatic Change, 2013)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Evolutionary rescue can prevent extinction following environmental change - Graham Bell; Andrew Gonzalez (Ecology Letters, 2009)
The ubiquity of global change and its impacts on biodiversity poses a clear and urgent challenge for evolutionary biologists. In many cases, environmental change is so widespread and rapid that individuals can neither accommodate to them physiologically nor migrate to a more favourable site. Extinction will ensue unless the population adapts fast enough to counter the rate of decline. According to theory, whether populations can be rescued by evolution depends upon several crucial variables: population size, the supply of genetic variation, and the degree of maladaptation to the new environment. Using techniques in experimental evolution we tested the conditions for evolutionary rescue (ER). Hundreds of yeast populations were exposed to normally lethal concentrations of salt in conditions, where the frequency of rescue mutations was estimated and population size was manipulated. In a striking match with theory, we show that ER is possible, and that the recovery of the population may occur within 25 generations. We observed a clear threshold in population size for ER whereby the ancestral population size must be sufficiently large to counter stochastic extinction and contain resistant individuals. These results demonstrate that rapid evolution is an important component of the response of small populations to environmental change.

Evolution of natural algal populations at elevated CO 2 - Sinéad Collins; Graham Bell (Ecology Letters, 2006)
Over the next century, it is expected that the concentration of CO 2 in the atmosphere will roughly double ( Watson et al. , 2001 , Climate Change 2001: the Scientific Basis , Intergovernmental Panel on Climate Change, Geneva). Microbial populations, which have large population sizes and short generation times, may respond to CO 2 enrichment through genetic change. Here we describe microalgae isolated from the soil of natural CO 2 springs and compare these strains with lines of Chlamydomonas that were selected at elevated CO 2 in the laboratory. Both the laboratory and natural populations failed to evolve specific adaptations to elevated CO 2 , and contain populations that grow poorly at ambient levels of CO 2 . Laboratory and CO 2 spring populations also include lines whose growth rates are insensitive to CO 2 . This demonstrates that, although laboratory selection experiments use simplified environments, the evolutionary responses that are seen following long‐term CO 2 enrichment correspond to those found in natural populations that have experienced similar conditions.

Resource competition and adaptive radiation in a microbial microcosm - R. Craig MacLean; Alison Dickson; Graham Bell (Ecology Letters, 2005)
Theory predicts that competition for shared resources in a monomorphic population generates divergent selection for adaptation to alternative resources. Experimental tests of this hypothesis are scarce. We selected populations of the bacterium Pseudomonas fluorescens in spatially homogeneous microcosms containing a complex mixture of resources. Initially, all populations consisted of two isogenic clones. The outcome of selection was the evolution of a diverse community of genotypes within each population. Sympatric genotypes exhibited differentiation in metabolic traits related to resource acquisition and frequency‐dependent trade‐offs in competitive ability, as we would expect if different genotypes consumed different resources. These results are consistent with the hypothesis of adaptive radiation driven by resource competition. Reconciling the results of this study with those of earlier experiments provides a new interpretation of the ecological causes of adaptive radiation in microbial microcosms.

Boron efficiency in oilseed rape: I. Genotypic variation demonstrated in field and pot grown Brassica napus L. and Brassica juncea L. - James C. R. Stangoulis; Harsharn S. Grewal; Richard W. Bell; Robin D. Graham (Plant and Soil, 2000)

An in vitro model of angiogenesis: Basic features - Eileen T. Bishop; Graham T. Bell; Stephen Bloor; I.J. Broom; Neil F.K. Hendry; Denys N. Wheatley (Angiogenesis, 1999)

WEDDELL SEAL ( LEPTONYCHOTES WEDDELLII ) FEEDING ON GENTOO PENGUINS ( PYGOSCELIS PAPUA ) - Norman D. Cobley; Graham Bell (Marine Mammal Science, 1998)

Differential response of oilseed rape (Brassica napus L.) cultivars to low boron supply - Jianming Xue; Minshu Lin; Richard W. Bell; Robin D. Graham; Xiaoe Yang; Yuai Yang (Plant and Soil, 1998)

Guinea pig maximisation test for skin sensitisation: the use of fewer test animals - Richard O. Shillaker; Graham M. Bell; John T. Hodgson; Michael D. J. Padgham (Archives of Toxicology, 1989)